2013
DOI: 10.1124/dmd.113.054833
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Function of the UDP-Glucuronosyltransferase 1A Subfamily by Cytochrome P450 3A4: Different Susceptibility for UGT Isoforms and UGT1A1/7 Variants

Abstract: Functional protein-protein interactions between UDPglucuronosyltransferase (UGT)1A isoforms and cytochrome P450 (CYP)3A4 were studied. To this end, UGT1A-catalyzed glucuronidation was assayed in Sf-9 cells that simultaneously expressed UGT and CYP3A4. In the kinetics of UGT1A6-catalyzed glucuronidation of serotonin, both Michaelis constant (K m ) and maximal velocity (V max ) were increased by CYP3A4. When CYP3A4 was coexpressed with either UGT1A1 or 1A7, the V max for the glucuronidation of the irinotecan met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 50 publications
(61 reference statements)
5
42
0
Order By: Relevance
“…Although many pairs of P450-UGT complexes can be formed (Ishii et al, 2007), we have particularly focused on a CYP3A4-UGT2B7 interaction, because these enzymes are involved in the metabolism of many drugs. The association of CYP3A4 and UGT2B7 has been confirmed by several biochemical techniques including coimmunoprecipitation and cross-linking (Takeda et al, , 2009Ishii et al, 2010Ishii et al, , 2014. Because CYP3A4 alters the regio-selectivity of UGT2B7-catalyzed morphine glucuronidation ) the binding of CYP3A4 and UGT2B7 is undoubtedly a functional interaction.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Although many pairs of P450-UGT complexes can be formed (Ishii et al, 2007), we have particularly focused on a CYP3A4-UGT2B7 interaction, because these enzymes are involved in the metabolism of many drugs. The association of CYP3A4 and UGT2B7 has been confirmed by several biochemical techniques including coimmunoprecipitation and cross-linking (Takeda et al, , 2009Ishii et al, 2010Ishii et al, , 2014. Because CYP3A4 alters the regio-selectivity of UGT2B7-catalyzed morphine glucuronidation ) the binding of CYP3A4 and UGT2B7 is undoubtedly a functional interaction.…”
Section: Introductionmentioning
confidence: 91%
“…After PstI treatment, CNX cDNA was also cloned into pFastBac1. The construction of pFastBac1-CYP3A4 was carried out as previously described (Ishii et al, 2014). For the pull-down assay, CYP3A4 having a carboxyl terminus tagged with hexahistidine (His-CYP3A4) was constructed by PCR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This modulation could be physiologically advantageous based on the roles of these enzymes in the sequential metabolism of xenobiotics. Recently, Ishii et al (2014) examined possible effects of CYP3A4 on UGT1A isoforms and concluded that the presence of CYP3A4 led to increases in UGT1A1 and UGT1A7 activities, while observing differential effects on the activities of allelic variants of these UGT isoforms (Ishii et al, 2014).…”
Section: Discussionmentioning
confidence: 99%